Beyond Weight Loss: Establishing a Postbariatric Surgery Patient Support Group—What Do Patients Want?. (14th February 2018) - Hameed, Saira; Salem, Victoria; Tan, Tricia M.; Collins, Alma; Shah, Krishna; Scholtz, Samantha; Ahmed, Ahmed R.; Chahal, Harvinder
Abstract : Purpose . There are limited resources for long-term specialist follow-up after bariatric surgery. In selected centres, patients can access a postoperative support group, but there is no clear evidence to guide their delivery. Materials and Methods . A retrospective study of bariatric surgery patients ( n  = 152) who had been discharged from specialist follow-up (mean time since surgery 5.5 years), covering weight history, physical and psychosocial comorbidities, and the need for a postoperative bariatric support group. Results . Fifty-eight percent wanted a postbariatric surgery patient support group. This was not associated with operation type or the amount of weight lost or regained. However, those who wanted a support group were significantly more likely to be struggling to keep the weight off, to be unhappy with the way they look, or to be experiencing difficulties returning to work. Conclusions . These data point to an unmet patient requirement for a postoperative support group that is independent of weight loss success. More research is required to ascertain how such a group should be delivered, but our data would suggest that supporting patients with weight loss maintenance, body image, and return to work is an important part of postoperative care, and these needs extend well beyond the immediate period of specialist follow-up.